2021
DOI: 10.3389/fcosc.2021.691900
|View full text |Cite
|
Sign up to set email alerts
|

Tiger Becomes Termite Hill: Soliga/Solega Perceptions of Wildlife Interactions and Ecological Change

Abstract: The Solega community living in the Biligiri Rangan Hills (B. R. Hills) of Karnataka State, southern India, have noticed significant changes to the ecosystem of their forest homeland over the last four or five decades. Originally hunter-gatherers, who carried out swidden agriculture at a subsistence level, they were forced to abandon the semi-nomadic ways of their ancestors, and settle in permanent villages when these forests were first declared a wildlife sanctuary in 1974. In this paper, we present the views … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Ecological studies and oral histories from BRT have shown forest change over the last few decades, due to erratic rainfall, climate change, and the widespread growth of invasive species such as Lantana camara (Sundaram et al, 2012). These changes have led to a sizeable loss of biodiversity, affecting access to the forest and the availability of forest produce, foods and medicinal plants historically used by Soligas (Agnihotri et al, 2021), who contend that the reduction in forest health is closely correlated to the banning of traditional management practices (Rai et al, 2018, and interview sources). For instance, they believe that traditional practices of burning leaf litter in ground-level fires called taragu benki, will help to reduce the growth of invasive plant species and regenerate the forest.…”
Section: The Contradictory Lives Of Youthmentioning
confidence: 99%
“…Ecological studies and oral histories from BRT have shown forest change over the last few decades, due to erratic rainfall, climate change, and the widespread growth of invasive species such as Lantana camara (Sundaram et al, 2012). These changes have led to a sizeable loss of biodiversity, affecting access to the forest and the availability of forest produce, foods and medicinal plants historically used by Soligas (Agnihotri et al, 2021), who contend that the reduction in forest health is closely correlated to the banning of traditional management practices (Rai et al, 2018, and interview sources). For instance, they believe that traditional practices of burning leaf litter in ground-level fires called taragu benki, will help to reduce the growth of invasive plant species and regenerate the forest.…”
Section: The Contradictory Lives Of Youthmentioning
confidence: 99%
“…Ideally, future studies will include a focus (not exclusively) on particular positive interactions and relations. This will extend beyond direct impacts of wildlife on humans and vice versa, and negative interactions, and look harder at nonrational factors influencing decision-making, including cultures and histories of human-wildlife interactions (see Pooley, 2016;Nijhawan and Mihu, 2020;Pooley et al, 2020;Agnihotri et al, 2021;Nair et al, 2021;Oommen, 2021).…”
Section: Elements Of Coexistencementioning
confidence: 99%
“…Further, cultures are dynamic, and do not provide static timeless ways of relating to and interpreting the natural world (Dickman et al, 2014;Bobo et al, 2015;Agnihotri et al, 2021;Oommen, 2021). What of people who abandon their traditional beliefs and practices (willingly or through force of circumstance), or hybridize them with other practices, in ways inimical to conservation (Nadasdy, 2005;Dickman et al, 2014)?…”
Section: Beyond a Conservation Framing Of Coexistencementioning
confidence: 99%